KRITERIA SERTIFIKASI HALAL BARANG GUNAAN DI INDONESIA - Jumiono, Aji; Siti Irma Rahmawati (Jurnal Ilmiah Pangan Halal, 2020)
Halal certification for utility goods is part of the mandatory provisions for halal certified products as contained in Law Number 33 of 2014 concerning Halal Assurance Product and its derivative regulations, namely in Government Regulation number 31 of 2019 and Regulation of the Minister of Religion Number 26 of 2019. The requirements used in the halal certification of used goods refers to the provisions of the halal certification criteria from the Indonesian Ulema Council and the LPPOM MUI as stipulated in the Decree of the Minister of Religion Number 982 of 2019 and the Decree of the Head of BPJPH Number 117 of 2019. The criteria used in the halal certification of used goods require compliance The Halal Assurance System according to the HAS 23000 standard which must guarantee that halal-certified products can maintain their halal consistency during the validity period of the halal certificate.